The Multifaceted Potential of Tirzepatide in Metabolic and Non-Metabolic Disorders - Mohamed, Thalal; Mahadevan, Srimathi; Prabhakaran, Jayashri Vidya; Venkatesan, Sundari; Fayaz, Mohammed; Mahalingam, Vijayakumar Thangavel (International Journal of Pharmaceutical Investigation, 2026)
Tirzepatide is redefining the treatment landscape for metabolic and non-metabolic disorders. By uniquely harnessing two critical hormonal pathways, the review provides comprehensive insights into how Tirzepatide’s dual mechanism of action sets it apart from existing therapies. Noteworthy findings from clinical and preclinical studies underscore Tirzepatide's potential in addressing complex conditions Highlighting its role in cardio protection, renal protection, neuroprotection, bone health in osteoporosis, reproductive health, respiratory health, genetic conditions management, cancer-associated weight gain, psychiatric illness and antipsychotic drug-induced obesity, inflammatory conditions, and other conditions. This comprehensive review not only underscores tirzepatide’s potential to address unmet clinical needs but also identifies key avenues for future research, aiming to elucidate its broader applicability and optimize patient outcomes. By highlighting these novel insights, this review positions tirzepatide as a transformative agent with the potential to redefine therapeutic paradigms across diverse medical domains.
Keywords: Tirzepatide; T2DM; Obesity; Metabolic Health; Bone Health Cardiovascular health; Reproductive Health; Neurological Health; Renal Health; Respiratory Health; Inflammatory conditions.